Jornalismo global, internacional ou regionalizado? Um estudo comparativo entre três edições digitais do El País – Espanha, Brasil e México - Siqueira, José Victor (2021)
This dissertation presents a comparative study of three digital editions of the newspaper El País – Spain, Brazil and Mexico – with the objective of investigating whether the slogan of “global periodicity”, used in all versions of the vehicle, represents a geographic scope, in terms coverage, or is it just a marketing expansion strategy of its founding group, PRISA. For this, the research rescues the historical and territorial trajectory of El País, from its emergence and consolidation as a reference diary in Spain, still in the 1970s, to its expansion to other European countries and the Americas over the following decades. Then, it carries out exploratory studies until it arrives at the configuration of a sample of 899 reports collected from the front pages of the three editions, between March 1st and 31st, 2021. The analysis criteria took into account the hierarchy of the news, the thematic incidence and the editorial framing of the same contents in the three editions, in order to identify journalistic similarities and differences between them, as well as their coherence or not with the postulate of “global journalism”. The analysis of the collected material is based upon a literature review on “global journalism”, “international journalism” and “comparative journalism”, as well as on the references of communication geographies. As a main conclusion, the research indicates that, instead of being global, the journalism practiced by El País is multiterritorial and regionalized by geocultural criteria (centered on Hispanic and Ibero-American cultures), which in Brazil competes with the socalled “national reference” newspapers.